Ethnomethodological studies of nurse-patient and nurse-relative interactions: A scoping review. (May 2017) - Mayor, Eric; Bietti, Lucas
Abstract: Objectives: Researchers in nursing science interested in the study of nurse-patient and nurse-relative interactions have displayed an ever increasing interest in ethnomethodology and conversation analysis. This review assesses the scope of this literature. We categorize the papers in thematic categories determined both inductively and deductively and synthesize the main findings of this literature within category. Finally we discuss the interactional determinants of the lack patient participation, the limitations of the field, and focus on implications. Design: A scoping review on nurse-patient and nurse-relative interactions. Data sources: Forty articles focusing on nurse-patient interactions and nurse-relative interactions. All the articles relied on ethnomethodology and/or conversation analysis. Review methods: A literature search has been carried out on Medline (all articles until June 2016; keywords were: nurs*.ab. and "conversation analysis"; nurs*.ab. and ethnomethodology). A similar search was performed on other platforms. The scope of the literature was identified by inductively and deductively analyzing the themes of the relevant articles. Results: Six thematic categories emerged: Organization of nurse-patient interaction (eleven articles); Organization of mediated nurse-patient interaction (seven articles); Information, explanation and advice (eight articles); Negotiation and influence asymmetry (six articles); Managing emotions in critical illness (two articles); and Interacting with patients presenting reduced interactional competences (six articles). Conclusions: Across most thematic categories it appeared that patient participation is far from ideal as interactional asymmetry was most observed in favor of nurses. When the encounters occurred at the patients' homes this pattern was reversed. Computer-mediated interactions were often reported as non-optimal as the standardized process constrained communication and delayed patients' presentation of their ailments. Micro-analyses of interaction present a clear potential for the development of guidelines for nurse-patient interactions. Implications for practice are described.